Can species distribution models be used to describe plant abundance patterns?. Issue 6 (7th November 2012) - Van Couwenberghe, Rosalinde; Collet, Catherine; Pierrat, Jean‐Claude; Verheyen, Kris; Gégout, Jean‐Claude
<x xml:space="preserve">Abstract</x> In recent years, there has been increasing interest in modelling of species abundance data in addition to presence data. In this study, we assessed the similarities and differences between presence‐absence distributions and abundance distributions along similar environmental gradients, derived, respectively, from presence‐absence and abundance data. Moreover, we examined the possibility of using presence‐absence distribution models to derive abundance distributions. For this purpose, we used Braun‐Blanquet abundance scores for 243 vascular species at 10 996 French forest sites. Species distribution models were used to analyse the link between the patterns of occurrence, low abundance and high abundance for each species with regard to mean annual temperature, June water balance, and soil pH. For each species, differences in the modelled distributions were characterised by the ecological optimum and ecological amplitude. A comparison of the presence‐absence and abundance distributions for all species revealed similar optima and different amplitudes along the three ecological factors. An abundant‐centre distribution was observed in environmental space, with species abundance being greatest at the optimal conditions and lower at less favourable conditions of the species occurrence response. Geographical habitat mapping also shows centred, high‐abundance suitability within the presence habitat of each species. We conclude that species distribution models derived from presence‐absence data provide useful information about the ecological optima of abundance distributions but overestimate the range of habitats suitable for high species abundance. This study demonstrates the utility of presence‐absence data for ecologist and conservation biologist when they are interested in the optimal conditions of high species abundance.